2000 tips for lecturers - edited by Phil Race (London Routledge, 1999)
Brings together a range of expert tips and guidance for all those lecturing and teaching in higher education. With ideas on all aspects of HE teaching, it covers a range of issues that can crop up in daily working life, and is both a lifeline to new teachers and a handy sourcebook and refresher for more experienced educators.
Includes index
Keywords: Lecturing